Islamic Family Law in Diaspora: Negotiating Gender and Marital Authority among Indonesian Muslim Immigrants in Sydney - Siti Zumrotun; Ilyya Muhsin; Adang Kuswaya; Sukron Ma’mun (Journal of Islamic Law, 2026)
This article examines how marital authority and gender relations are negotiated among Indonesian Muslim immigrant families in Sydney within the framework of Islamic family law. While Muslim family norms are often portrayed as uniform, migration to multicultural societies creates new contexts in which Islamic legal doctrines are interpreted and practised in diverse ways. This study, therefore, investigates how key concepts of Islamic family law—qiwāmah (leadership), nafaqah (financial maintenance), ṭāʿah (spousal obligation), shūrā (consultation), and muʿāsharah bi al-maʿrūf (equitable marital relations)—are understood and implemented in Muslim immigrant households. Employing a qualitative socio-legal approach, the research draws on fieldwork and in-depth interviews with Indonesian Muslim immigrant couples in Sydney, complemented by participant observation and doctrinal analysis of Islamic legal texts. The findings identify five patterns of marital relations: owner–property, head–complement, senior–junior partner, equal partner, and equity–equality partner. These relational models reflect different interpretations of Islamic legal authority, ranging from hierarchical readings of qiwāmah to more reciprocal and justice-oriented understandings grounded in maqāṣid al-sharīʿah. The study demonstrates that migration operates as a space of legal negotiation in which Islamic family norms are neither abandoned nor mechanically preserved but continuously reinterpreted through processes of contextual reasoning and everyday marital practice. By linking empirical family dynamics with Islamic legal interpretation, this research contributes to socio-legal scholarship on the transformation of Sharīʿah in minority and diasporic contexts. [Artikel ini menganalisis bagaimana otoritas perkawinan dan relasi gender dinegosiasikan dalam keluarga imigran Muslim Indonesia di Sydney dalam kerangka hukum keluarga Islam. Meskipun norma keluarga Muslim sering dipandang bersifat seragam, migrasi ke masyarakat multikultural menghadirkan konteks baru di mana doktrin hukum Islam ditafsirkan dan dipraktikkan secara beragam. Penelitian ini bertujuan untuk mengkaji bagaimana konsep-konsep utama dalam hukum keluarga Islam—qiwāmah (kepemimpinan), nafaqah (nafkah), ṭāʿah (ketaatan), shūrā (musyawarah), dan muʿāsharah bi al-maʿrūf (hubungan yang baik)—dipahami dan dijalankan dalam rumah tangga Muslim di diaspora. Penelitian ini menggunakan pendekatan kualitatif sosio-legal melalui kerja lapangan dan wawancara mendalam dengan pasangan imigran Muslim Indonesia di Sydney, yang dilengkapi dengan observasi partisipatif serta analisis doktrinal terhadap literatur hukum Islam. Hasil penelitian mengidentifikasi lima pola relasi perkawinan, yaitu model berbasis harta, kepala-komplementer, mitra senior-junior, mitra setara, dan mitra setara-adil. Pola-pola tersebut mencerminkan beragam interpretasi terhadap otoritas dalam hukum keluarga Islam, mulai dari pembacaan hierarkis terhadap konsep qiwāmah hingga pemahaman yang lebih resiprokal dan berorientasi pada keadilan berdasarkan pendekatan maqāṣid al-sharīʿah. Temuan ini menunjukkan bahwa migrasi menjadi ruang negosiasi hukum di mana norma-norma keluarga Islam tidak sekadar dipertahankan atau ditinggalkan, tetapi terus ditafsirkan ulang melalui proses ijtihad kontekstual dan praktik kehidupan keluarga sehari-hari. Dengan menghubungkan dinamika keluarga Muslim di diaspora dengan interpretasi hukum Islam, penelitian ini memberikan kontribusi bagi kajian sosio-legal mengenai transformasi syariat dalam konteks masyarakat minoritas dan diaspora.]